2004
DOI: 10.1242/dev.01517
|View full text |Cite
|
Sign up to set email alerts
|

INCOMPOSITA: a MADS-box gene controlling prophyll development and floral meristem identity inAntirrhinum

Abstract: INCOMPOSITA (INCO) is a MADS-box transcription factor and member of the functionally diverse StMADS11 clade of the MADS-box family. The most conspicuous feature of inco mutant flowers are prophylls initiated prior to first whorl sepals at lateral positions of the flower primordium. The developing prophylls physically interfere with subsequent floral organ development that results in aberrant floral architecture. INCO, which is controlled by SQUAMOSA, prevents prophyll formation in the wild type, a role that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 39 publications
8
104
0
Order By: Relevance
“…4 B and C). These results, together with the known function of SVP genes as suppressors of flowering and inflorescence development (30)(31)(32)(33), suggest that the three SVP genes work downstream of TAW1 to suppress SM identity. Using a two-component induction system, we confirmed that the induction of TAW1 transcription does indeed lead to the activation of the three SVP genes (Fig.…”
Section: Taw1 Is Expressed In the Meristem To Suppress The Transitionmentioning
confidence: 75%
“…4 B and C). These results, together with the known function of SVP genes as suppressors of flowering and inflorescence development (30)(31)(32)(33), suggest that the three SVP genes work downstream of TAW1 to suppress SM identity. Using a two-component induction system, we confirmed that the induction of TAW1 transcription does indeed lead to the activation of the three SVP genes (Fig.…”
Section: Taw1 Is Expressed In the Meristem To Suppress The Transitionmentioning
confidence: 75%
“…This subclade includes only two Arabidopsis genes, SVP and AGL24. Ectopic overexpression of SVP and related genes in Arabidopsis leads to foliose sepal syndrome-that is, the formation of large sepals 22 . In apple, this specific subclade not only includes two genes expressed in the pome but is also expanded to include 15 other genes.…”
Section: G T a A C C G G T T G T A C C T A G C T A G A C G T A A C mentioning
confidence: 99%
“…To confirm the T-DNA insertion sites of these alleles, we sequenced the PCR products amplified using left border primers and gene-specific primers. SVP overexpressor plants obtained from H. Sommer (Max Planck Institut, Köln, Germany) have been described previously (Masiero et al 2004). The mutant lines used in this study are described in Supplementary Table S1.…”
mentioning
confidence: 99%